2022
DOI: 10.3389/fpsyt.2022.990465
|View full text |Cite
|
Sign up to set email alerts
|

Combined probiotics attenuate chronic unpredictable mild stress-induced depressive-like and anxiety-like behaviors in rats

Abstract: Increasing evidence indicated that probiotics can be effective in improving behaviors similar to depression and anxiety disorders. However, the underlying mechanisms remain unclear, as is the effects of single vs. combined probiotics on depression and anxiety. This study aimed to determine whether combined probiotics could attenuate depressive-like and anxiety-like behavior induced by chronic unpredictable mild stress (CUMS) and its potential mechanisms. Rats underwent CUMS treatment and then administered Lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 63 publications
5
16
0
Order By: Relevance
“…In the antibiotic‐mediated microbiota‐depletion mouse model, ampicillin, gentamicin, metronidazole, neomycin (all at 0.25 mg/day), and vancomycin (0.125 mg/day) were given to all mice for 14 days to deplete gut microbiota. After a three‐day washout period, the recipient Control + Con‐FMT group and Model + Con‐FMT group mice were given 200 μL of donor supernatant from Control group and Model + Zzcd‐FMT group mice were given 200 μL of donor supernatant from ZZCD group by oral gavage every 2 days for 2 weeks 27,28 . The behavioral tests were performed for four consecutive days from FMT week 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the antibiotic‐mediated microbiota‐depletion mouse model, ampicillin, gentamicin, metronidazole, neomycin (all at 0.25 mg/day), and vancomycin (0.125 mg/day) were given to all mice for 14 days to deplete gut microbiota. After a three‐day washout period, the recipient Control + Con‐FMT group and Model + Con‐FMT group mice were given 200 μL of donor supernatant from Control group and Model + Zzcd‐FMT group mice were given 200 μL of donor supernatant from ZZCD group by oral gavage every 2 days for 2 weeks 27,28 . The behavioral tests were performed for four consecutive days from FMT week 2.…”
Section: Methodsmentioning
confidence: 99%
“…After a threeday washout period, the recipient Control + Con-FMT group and Model + Con-FMT group mice were given 200 μL of donor supernatant from Control group and Model + Zzcd-FMT group mice were given 200 μL of donor supernatant from ZZCD group by oral gavage every 2 days for 2 weeks. 27,28 The behavioral tests were performed for four consecutive days from FMT week 2. Blood samples from the mice orbit was used for ELISA.…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%
“…Indeed, some stress‐induced changes in gut physiology have been prevented or reversed by administration of Lactobacillus spp. (Huang et al., 2022; Jang et al., 2018; Li et al., 2019; Zareie et al., 2006) or Bifidobacterium spp. (Huang et al., 2022; Li et al., 2019; Tian, O'Riordan et al., 2020) in rodents.…”
Section: The Stress Response: From Adaptation To Diseasementioning
confidence: 99%
“…(Huang et al., 2022; Jang et al., 2018; Li et al., 2019; Zareie et al., 2006) or Bifidobacterium spp. (Huang et al., 2022; Li et al., 2019; Tian, O'Riordan et al., 2020) in rodents. Additionally, emerging preclinical evidence indicates that stress exposure enriches pathogenic bacteria, such as Escherichia‐Shigella (Jang et al., 2018; Shaler et al., 2021).…”
Section: The Stress Response: From Adaptation To Diseasementioning
confidence: 99%
“…Our previous studies have found that chronic unpredictable mild stress (CUMS) stimuli induced depression-like behaviors, increased levels of IL-1β and IL-18 and altered the microbiota ( Huang et al., 2022 ), which suggested NLRP3 inflammasome might be activated. What’s more, intervention with combined probiotic reversed altered microbiota and reduced levels of inflammatory cytokines, further indicating that microbiota might be a key role in activating NLRP3 inflammasome and upregulating inflammation ( Mou et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%